2007
DOI: 10.1124/mol.107.036889
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Alters the Cellular Responsiveness to Clopidogrel, Irinotecan, and Oseltamivir by Suppressing the Expression of Carboxylesterases HCE1 and HCE2

Abstract: Carboxylesterases constitute a class of enzymes that play important roles in the hydrolytic metabolism of drugs and other xenobiotics. Patients with liver conditions such as cirrhosis show increased secretion of proinflammatory cytokines [e.g., interleukin-6 (IL-6)] and decreased capacity of hydrolysis. In this study, we provide a molecular explanation linking cytokine secretion directly to the decreased capacity of hydrolytic biotransformation. In both primary hepatocytes and HepG2 cells, treatment with IL-6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 31 publications
1
57
0
2
Order By: Relevance
“…Clone A cells are derived from Huh7 cells, a hepatoma cell line that is permissive for HCV replicon replication (26). The suppression of CES1 may be common in hepatoma cell lines; Yang et al (27) have previously reported that HepG2 cells, another hepatoma cell line, expressed much lower levels of CES1 than primary hepatocytes. Telaprevir, which was found to be an inhibitor of CatA, inhibited the metabolism of PSI-7851 in clone A.…”
Section: Discussionmentioning
confidence: 99%
“…Clone A cells are derived from Huh7 cells, a hepatoma cell line that is permissive for HCV replicon replication (26). The suppression of CES1 may be common in hepatoma cell lines; Yang et al (27) have previously reported that HepG2 cells, another hepatoma cell line, expressed much lower levels of CES1 than primary hepatocytes. Telaprevir, which was found to be an inhibitor of CatA, inhibited the metabolism of PSI-7851 in clone A.…”
Section: Discussionmentioning
confidence: 99%
“…It includes human intestinal CE (CES2A1), 34,[40][41][42][43][44] rat CES2 (CES2A10), 22) rat intestinal CE RL4 (rCES2) (CES2A6), 45) rabbit form 2 46) and hamster AT51 (CES2A11). 47) CES3 includes ES-male (CES3A2) and human CES3 (CES3A1).…”
Section: Novel Classification and Nomenclature Of Mammalian Cesunclassified
“…It includes human intestinal CarbE (CES2A1) (Schwer et al, 1997;Humerickhouse et al, 2000;Imai et al, 2006;Taketani et al, 2007;Yang et al, 2007;Shi et al, 2008), rCES2 (CES2A10) (Furihata et al, 2005), rat intestinal CarbE RL4 (rCES2) (CES2A6) (Furihata et al, 2003), rabbit form 2 (Ozols, 1989) and hamster AT51 (CES2A11) (Sone et al, 1994). CES3 includes ES-male (CES3A2) and human CES3 (CES3A1) (Aida et al, 1993;Sanghani et al, 2004).…”
Section: Introductionunclassified